(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the quality of education and the diversity of methods and perspectives of development stages. Also the article shows the processes of teaching and educating the students with the help of what kind of methods in the moders pedagogical situation. The teaching methodology is aimed at activating teaching methods, the process of educational and cognitive activity, strengthens it. The teaching methodology is aimed at activating teaching methods, the process of educational and cognitive activity, strengthens it.